Foucault: His Thought, His Character - Maynard, Steven (Labour / Le Travail, 2012)
The article reviews the book, "Foucault: His Thought, His Character," by Paul Veyne, translated by Janet Lloyd.
Keywords: BOOKS – Reviews; FOUCAULT; Michel; 1926-1984; FOUCAULT: His Thought; His Character (Book); Nonfiction; VEYNE; Paul